2016
DOI: 10.1016/j.jep.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Channa striatus cream down-regulates tumour necrosis factor (TNF)-alpha gene expression and alleviates chronic-like dermatitis in mouse model

Abstract: Haruan is an effective topical anti-inflammatory agent in this mouse model of chronic-like dermatitis, thus suggesting its potential as a non-steroidal treatment option for chronic inflammatory dermatoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Therefore, the aqueous extract of C. striatus could inhibit monocyte infiltration and fibroblast proliferation; these may potentially prevent atherosclerosis development. respectively; these effects were comparable to 1% hydrocortisone administration of these doses of C. striatus cream also down-regulated TNF- gene expression level to 34, 54, and 112-fold respectively, with significant reduction as compared to TPA (negative control) alone [18]. Based on the studies highlighted, it could be deduced that the anti-inflammatory effects of C. striatus is attributed to the inhibition of the pro-inflammatory cytokine, TNF- production.…”
Section: Anti-inflammatory Propertymentioning
confidence: 57%
See 2 more Smart Citations
“…Therefore, the aqueous extract of C. striatus could inhibit monocyte infiltration and fibroblast proliferation; these may potentially prevent atherosclerosis development. respectively; these effects were comparable to 1% hydrocortisone administration of these doses of C. striatus cream also down-regulated TNF- gene expression level to 34, 54, and 112-fold respectively, with significant reduction as compared to TPA (negative control) alone [18]. Based on the studies highlighted, it could be deduced that the anti-inflammatory effects of C. striatus is attributed to the inhibition of the pro-inflammatory cytokine, TNF- production.…”
Section: Anti-inflammatory Propertymentioning
confidence: 57%
“…C. striatus has been demonstrated to exert several pharmacological activities [11,12], majorly attributed to its high content of essential amino acids and fatty acids [13,14]. Previous studies have reported C. striatus to have hypoglycemic [15], antioxidant [16], anti-inflammatory [11,[17][18][19], antinociceptive [12,[20][21][22], anti-bacterial [23,24], wound healing [25][26][27][28][29], and anti-ulcer [8,30] properties. Therefore, this review aims to provide an overview of the pharmacological properties of C. striatus related to diabetes and cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be seen from the results of a study conducted by Adam et al, which stated that the application of snakehead fish extract significantly reduced the expression of TNF-α [20]. The results of the study by Isa et al concluded that snakehead fish is an effective topical anti-inflammatory agent in a mouse model with chronic inflammation [21]. It is still largely unknown which bioactive compounds from snakehead fish are involved in the anti-inflammatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some researchers have studied about the benefits of snakehead fish for reducing inflammation. Local people believed that snakehead fish reduces pain and use it mostly for treating mothers after delivery and any post-operative pain, 7 wound healing, 5,[8][9] anti-eczema, 10 and platelet aggregation 2 are some wellknown pharmacological properties of snakehead fish are demonstrated till now. Glycine is one of the amino acids which have the highest content in SFP.…”
Section: Introductionmentioning
confidence: 99%